2017
DOI: 10.3892/ol.2017.6561
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-346 promotes proliferation, migration and invasion in liver cancer

Abstract: Abstract. Liver cancer primarily accounts for the majority of malignancies of the liver. MicroRNAs (miRNAs) are endogenous non-coding RNAs, which are important in tumorigenesis. Abnormal expression of microRNA-346 (miR-346) has been demonstrated in various types of human cancer, however, its expression and potential molecular mechanism in liver cancer remains to be elucidated. Expression levels of miR-346 in liver cancer cell lines were determined by quantitative polymerase chain reaction. The effect of miR-34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 33 publications
(34 reference statements)
1
14
1
Order By: Relevance
“…Similarly, the downregulation of miR-346 led to an activation of the proliferation, migration and invasion of gestational choriocarcinoma cells, and this phenomenon was also be reversed by siLRP6 treatment. miR-346 is known to have a tumor-promoter function in a variety of tumor cells, including in liver cancer (27), nasopharyngeal cancer (28), and breast cancer (29). However, contrary to previous findings, the present study revealed that downregulated miR-346 promoted the proliferation, migration and invasion of trophoblast cells.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, the downregulation of miR-346 led to an activation of the proliferation, migration and invasion of gestational choriocarcinoma cells, and this phenomenon was also be reversed by siLRP6 treatment. miR-346 is known to have a tumor-promoter function in a variety of tumor cells, including in liver cancer (27), nasopharyngeal cancer (28), and breast cancer (29). However, contrary to previous findings, the present study revealed that downregulated miR-346 promoted the proliferation, migration and invasion of trophoblast cells.…”
Section: Discussioncontrasting
confidence: 99%
“…Its role is important in the case of cancer biology; several studies showed its oncogenic nature in numerous cancers, which was responsible for promotion of the more aggressive phenotype of disease. It has been shown that overexpression of hsa-miR-346 promoted cell proliferation, colony formation, migration, invasion in nasopharyngeal, colorectal, and liver cancer [32][33][34][35]. Moreover, it was responsible for reduced apoptosis and resistance to docetaxel of breast cancer cells [36] Most of the downregulated miRNAs detected in our study in the metastatic patient subgroup belong to the miRNA-506-513 cluster, which is consistent with previous TCGA-based studies [5,18].…”
Section: Discussionsupporting
confidence: 89%
“…On the contrary, miR-21 can promote the proliferation of liver cancer, whose mechanism may be related to the direct targeted inhibition of miR-21 on MAP kinase-kinase 3 (MAP2K3) (18). Moreover, miR-346 also serves as a cancer-promoting gene, which can facilitate the proliferation, invasion and metastasis of liver cancer cells through targeted inhibition on F-Box and leucine-rich repeat protein (FBXL2) (19). In the present study, it was found for the first time, to the best of our knowledge, that the miR-101 expression level in liver cancer tissues was significantly lower than that in para-carcinoma tissues, indicating that miR-101 may play a role as a cancer suppressor gene.…”
Section: Discussionmentioning
confidence: 99%